Sources of Arterial Vascularization of the Polar Owl’s Kidneys - V. Pervenetskaya , Marina; V. Fomenko, Lydmila; V. Koshkarev, Maksim (KnE Life Sciences, 2021)
The sources of vascularization of the kidneys of five polar owl carcasses were studied by filling the vessels with self-hardening plastic Belokril through the femoral artery. High-grade oil paints were added to the monomer to give the vessels the desired color. After the injection, the carcasses were placed in a high concentration caustic soda solution for three days. The resulting corrosion impression was washed under warm water and dried. It was identified that in the lumbar trunk, the main vessel was the descending aorta, from which extra- and intraorganic arteries departed for vascularizing the kidneys. Extraorganic arteries included external and internal iliac, sciatic and middle sacral arteries. Intraorganic arteries included cranial, middle, and caudal renal arteries. Inside the parenchyma of each lobe of the kidney, intraorganic arteries branched in the main type of caudomedial, dorsomedial and lateromedial directions and were subdivided into segmental, interlobular and perilobular arteries and intralobular capillaries. An asymmetry in the branching of the renal arteries was observed. During histological examination, we noted that the renal arteries were lined with endothelium on the inner side and the intima contained endotheliocytes with oval nuclei. Under the endothelial layer were loose collagen fibers running along the middle shell. There was no loose connective tissue between the inner and middle shells, so the subendothelial layer was very weak and there was no internal elastic membrane. The muscle membrane was well developed, with collagen and elastic fibers located between the muscle fibers. The outer shell was represented by loose connective tissue with the presence of arterial and venous vessels. The collagen fibers had a slightly convoluted course. Keywords: birds, polar owl, arteries, kidneys, parenchyma, capillaries, endotheliocytes, intima